2017
DOI: 10.3389/fpsyg.2017.00011
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Abbreviated Math Anxiety Scale: A Valid and Reliable Instrument for Use with Children

Abstract: Mathematics anxiety (MA) can be observed in children from primary school age into the teenage years and adulthood, but many MA rating scales are only suitable for use with adults or older adolescents. We have adapted one such rating scale, the Abbreviated Math Anxiety Scale (AMAS), to be used with British children aged 8–13. In this study, we assess the scale's reliability, factor structure, and divergent validity. The modified AMAS (mAMAS) was administered to a very large (n = 1746) cohort of British children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
159
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(183 citation statements)
references
References 41 publications
15
159
1
8
Order By: Relevance
“…Similar indices of construct, convergent and discriminant validities were reported in other language versions, including Farsi (e.g., .61 correlation with statistics anxiety measure; Vahedi & Farrokhi, 2011), Italian (e.g., .57 correlation with test anxiety; Primi et al, 2014;.32 correlation with the physiological anxiety subscale; Caviola et al, 2017) and Polish (e.g., .33 correlation with trait anxiety; Cipora et al, 2015aCipora et al, , 2015b. Carey, Hill, et al (2017) in a large scale study by means of item-level factor analyses showed that (slightly modified) AMAS items loaded on a separate factor among other factors representing other types of anxiety (varied aspects of general anxiety and test anxiety).…”
Section: Validitymentioning
confidence: 70%
See 4 more Smart Citations
“…Similar indices of construct, convergent and discriminant validities were reported in other language versions, including Farsi (e.g., .61 correlation with statistics anxiety measure; Vahedi & Farrokhi, 2011), Italian (e.g., .57 correlation with test anxiety; Primi et al, 2014;.32 correlation with the physiological anxiety subscale; Caviola et al, 2017) and Polish (e.g., .33 correlation with trait anxiety; Cipora et al, 2015aCipora et al, , 2015b. Carey, Hill, et al (2017) in a large scale study by means of item-level factor analyses showed that (slightly modified) AMAS items loaded on a separate factor among other factors representing other types of anxiety (varied aspects of general anxiety and test anxiety).…”
Section: Validitymentioning
confidence: 70%
“…Apart from the total score, AMAS comprises two scales: (1) anxiety related to learning math (Learning), and (2) anxiety related to being tested in math (Testing). This structure was confirmed in several samples using both exploratory and confirmatory factor analyses (e.g., Hopko et al, 2003;Cipora et al, 2015aCipora et al, , 2015b Hill, et al, 2017). It was also used in studies on English speaking younger adolescents (11 years and older, however reliability estimates for this age group were not provided; Devine et al, 2012).…”
mentioning
confidence: 92%
See 3 more Smart Citations